A Study on the Effectiveness of Cost Reduction Strategies on Operational Efficiency at Bajaj Auto Limited, Nagpur - Bhalchandra Patle, Abhay; Tekade, Atul B (Journal of Neonatal Surgery, 2025)
Cost reduction strategies play a pivotal role in enhancing operational efficiency, particularly in highly competitive industries like automotive manufacturing. This study evaluates the effectiveness of various cost reduction measures implemented at Bajaj Auto Limited, Nagpur, focusing on their influence on productivity, resource optimization, and financial performance. The research employs both quantitative and qualitative methodologies, analysing financial data, operational metrics, and employee feedback to identify the impact of these strategies. Key findings reveal that targeted cost-saving initiatives in procurement, inventory management, and energy consumption substantially reduce operational costs without compromising quality. Furthermore, the study highlights the importance of employee engagement and technological advancements in sustaining long-term efficiency gains. The analysis provides actionable insights for organizations aiming to align cost management practices with strategic objectives, ensuring a balance between expenditure control and operational excellence. By presenting a comprehensive overview of cost reduction approaches and their outcomes, the research contributes to the growing discourse on sustainable efficiency in the automotive sector.